Treatment of myopic choroidal neovascularization with intravitreal ranibizumab injections: the role of age - Karagiannis, Dimitrios (Clin Ophthalmol, 2017)
PURPOSE: The aim of this study was to explore the role of age as a prognostic factor for the outcome of myopic choroidal neovascularization (CNV) treatment with intravitreal ranibizumab injections. METHODS: A retrospective review of charts of patients treated with intravitreal injections of ranibizumab for the treatment of myopic CNV was done. Patients with other ophthalmic disease were excluded. Patients were followed for at least 2 years. The correlation between age and the change in visual acuity and the number of injections during treatment was investigated. RESULTS: Age of the patients was significantly correlated with the number of injections that the patients received (Pearson’s r=0.585, P=0.005). Also, it was significantly correlated with improvement in corrected distance visual acuity, defined as the difference between final and initial LogMAR corrected distance visual acuity (Pearson’s r=0.614, P=0.003). CONCLUSION: Age significantly affects the visual outcome of myopic CNV treatment with ranibizumab. Younger patients in our study needed fewer intravitreal injections and achieved a more significant improvement in vision.